A Relação entre unidade de conservação e governança a partir da área fronteiriça entre Brasil e Bolívia - SANTOS, Adria Macedo dos (Universidade Federal do Pará, 2023)
This thesis deals with environmental governance in protected areas and their surroundings, located in the Amazon context, more precisely in the border zone between Brazil and Bolivia. The investigation consists of looking for answers regarding how the social actors who participate directly or indirectly in PA, articulate and enable collective and specific actions, in order to positively impact the construction of governance in these areas, with a view to biodiversity conservation. The study starts from the hypothesis that, although the bases that establish an environmental governance process in the PAs are defined by the State, the participation of social actors is a determining condition for the preservation of its ecosystem. That said, it should be noted that the research aims to comparatively analyze the construction of environmental governance from the perspective of collective action in: ESEC Taiamã and Guajará-Mirim State Park (PEGM), in Brazil, and Parque Nacional Noel Kempff Mercado (PNNKM), in Bolivia, to consider, mainly, what is done by various social actors with regard to the conservation of these units. For this, it was based on theoretical notions that address the concept and application of environmental governance, conservation units, sustainability and their connections with social participation. The methodological bases of this thesis are based on qualitative research, the corpus of the analysis was constituted based on primary data, bibliographical sources, field research, interviews and photographic records. The results reveal, in summary, that the participation and engagement of social actors in these PAs are crucial for the governance process and the protection of biodiversity.